Islamic political ethics in advice literature : Ibn Qutaybah and his kitab al-Sultan of Uyun al-Akhbar - Risallah, Fiqih (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2011)
This present study is designed to focus on Islamic political ethics in advice literature and takes Kitāb al-SulÏān of Ibn Qutayabah's Uyūn al-Akhbār as the object of the study. It aims to expound the ethical principles in it and outline it on the basis of political practices. In fact, some scholars of Islamic political thought, both Muslims and non-Muslims alike, less appreciate this work, along with its similar types. Having the elements of Mirrors for Princes Genre notwithstanding, Kitāb al-Sultan of Uyūn al-Akhbār was not classified by some as a Mirror work. Yet, for others, they objectively see it as such and further argue that, with other similar works, it has its own merit in forming the theory of Islamic polity in general. For this, the discussion in the first chapter traces the genre of Mirrors for Princes and its development in Islamic advice literature, so as to clarify the Uyūn al-Akhbār's genre; with Ibn Qutaybah's life and works briefly presented. The second chapter is the core study expounding all the ethical qualities found in Kitāb al-SulÏān, under three spectrums of discussion. Qualities within the spectrum on the practice of political authority are presented in fourteen topics, related to governmental and administrative circles. There are three dispositions pointed out within the second spectrum that Ibn Qutaybah tried to remind us in his book, which accordingly can abuse the political power such as following passion, oppression, and disloyalty. To overcome all of these, within the third spectrum on principles of political actions, Ibn Qutaybah puts an emphasis on uplifting the religious values such as justice, enjoining good and forbidding evil, trustworthy, moderation, and responsibility for those who engage in practical conduct of governance, the ruler and the ruled, in order to obtain success in managing public affairs. In chapter three, the discussion is on Ibn Qutaybah's contribution to Islamic political thought. It analyzes his method of assimilating the values of the great traditions, which are of course in conformity with Islamic teaching, as indicated in Kitāb al-SulÏān. What he meant was an adjustment of the wisdom prevalent in the Persian and other lore into Muslim understanding. Still, in this chapter, the study then makes reflections of his ethical qualities on the contemporary significance, which are relevant to today's politics. In this respect, his mirror work, Kitāb al-SulÏān, is also a kind of refinement and remedy for contemporary political paucity. This study subsequently arrives at the conclusion that, according to Ibn Qutaybah, religiosity with its ethical values is of the utmost importance in an Islamic polity, for it will therefore lead with God's grace to success here on earth as well as in the hereafter.